Social equity and ecological sustainability: Can the two be achieved together? - Thomas Kopp; Franziska Dorn (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2018)
Two of the greatest challenges facing societies today are the rapid deterioration of the natural environment as well as high levels of economic inequality. Policies addressing these two challenges are often designed independent of each other, neglecting their interconnected nature. Therefore, designing better policies requires a profound knowledge of this potential trade-off. Until now, however, the characteristics of this trade-off have remained unclear, as little empirical research is available. This paper fills this gap by conceptualizing the trade-off through a macroeconomic model and estimating it empirically. It is the first paper to develop a microeconomically-based model of consumption that includes two transmission channels of inequality on biosphere use: First, the income-effect refers to the non-linear, decreasing impact of rising incomes on consumption spending after subsistence needs are fulfilled, which leads to a negative correlation between levels of inequality and pollution levels. Second is the effect of conspicuous consumption, which can reverse the tendency towards increased pollution caused by the income-effect. The empirical application assesses which of these opposing mechanisms prevails. The model is estimated by the Group Fixed Effects estimator, based on an unbalanced panel of 167 countries over 33 years. To account for the multidimensionality of biosphere use it is measured by the disaggregated components of the Ecological Footprint. Results indicate that the income effect prevails over the conspicuous consumption effect, meaning that there is indeed a trade-off between reducing biosphere use and inequality levels. This means for policy makers that measures to reduce inequality need to be accompanied by policies that limit harmful environmental impacts of redistribution. Since three of the Ecological Footprint's sub-indices refer to food consumption, the analysis also yields interesting conclusions on the relationship between inequality and food security.
Keywords: 330